Draft Annual Plan 1989-90 Union Territory of Dadra and Nagar Haveli - Planning Commission (Planning Commission, 1989)
The ongoing schemes of Animal Husbandry and Dairy Development will continue during the Plan period. New schemes, such as rearing of female buffalo calves, adoption of frozen semen technique for cattle development providing live stock marketing facilities etc. have been introduced. With the commissioning of Damanganga Project, it is proposed to take up fishery scheme by making use of the water in the reservoir and the canals.
Planning Division, Union Territory of Dadra and Nagar Haveli